2017
DOI: 10.1063/1.4983304
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase anion photoelectron spectroscopy and theoretical investigation of gold acetylide species

Abstract: We conducted gas phase anion photoelectron spectroscopy and density functional theory studies on a number of gold acetylide species, such as AuCH, AuCAu, and AuCH. Based on the photoelectron spectra, the electron affinities of AuCH, AuCAu, and AuCH are measured to be 1.54(±0.04), 1.60(±0.08), and 4.23(±0.08) eV, respectively. The highest occupied molecular orbital-lowest unoccupied molecular orbital (HOMO-LUMO) gaps of AuCH and AuCAu are measured to be about 2.62 and 2.48 eV, respectively. It is interesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 81 publications
(79 reference statements)
1
4
0
Order By: Relevance
“…As a comparison, we have investigated a series of AuC 2n − and AuC 2n H − species 24,25 using high-resolution PES based on a velocity-map imaging (VMI) instrument 26 and confirmed the strong influence of the auxiliary ligand on the Au− −C bonds in LAuCCH − . A similar study on AuC 4 H − , 27 as well AuC 2 H − and Au 2 C 2 − , 28 has recently been reported at lower resolution.…”
Section: Introductionsupporting
confidence: 74%
“…As a comparison, we have investigated a series of AuC 2n − and AuC 2n H − species 24,25 using high-resolution PES based on a velocity-map imaging (VMI) instrument 26 and confirmed the strong influence of the auxiliary ligand on the Au− −C bonds in LAuCCH − . A similar study on AuC 4 H − , 27 as well AuC 2 H − and Au 2 C 2 − , 28 has recently been reported at lower resolution.…”
Section: Introductionsupporting
confidence: 74%
“…In this way, the ADE value of PtC n – and PtC n N 2 – ( n = 4–6) is evaluated to be 3.34 ± 0.07 (PtC 4 – ), 2.53 ± 0.11 (PtC 5 – ), 3.65 ± 0.05 (PtC 6 – ), 3.67 ± 0.05 (PtC 4 N 2 – ), 2.80 ± 0.09 (PtC 5 N 2 – ), and 3.93 ± 0.04 eV (PtC 6 N 2 – ) (Table ), respectively. Interestingly, a larger gap between the ground state peak and the excited state peak was observed in the spectra of PtC 5 – and PtC 5 N 2 – as compared with other species, indicating that the PtC 5 and PtC 5 N 2 neutrals have a large gap between their highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital. …”
Section: Results and Analysismentioning
confidence: 99%
“…The photoelectron spectra were calibrated using the known spectrum of [Au] − . 67 The energy resolution was better than 5%, corresponding to 50 meV at an electron kinetic energy of 1 eV.…”
Section: Methodsmentioning
confidence: 97%
“…The photoelectrons are detected by a microchannel plate/phosphor screen combination, and the photoelectron images are collected by a charge-coupled device camera. The photoelectron spectra were calibrated using the known spectrum of [Au] − . The energy resolution was better than 5%, corresponding to 50 meV at an electron kinetic energy of 1 eV.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%